Imaging brain mechanisms in chronic visceral pain. Issue 1 (April 2015) - Mayer, Emeran A.; Gupta, Arpana; Kilpatrick, Lisa A.; Hong, Jui-Yang
Abstract : Abstract: Chronic visceral pain syndromes are important clinical problems with largely unmet medical needs. Based on the common overlap with other chronic disorders of visceral or somatic pain, mood and affect, and their responsiveness to centrally targeted treatments, an important role of central nervous system in their pathophysiology is likely. A growing number of brain imaging studies in irritable bowel syndrome, functional dyspepsia, and bladder pain syndrome/interstitial cystitis has identified abnormalities in evoked brain responses, resting state activity, and connectivity, as well as in gray and white matter properties. Structural and functional alterations in brain regions of the salience, emotional arousal, and sensorimotor networks, as well as in prefrontal regions, are the most consistently reported findings. Some of these changes show moderate correlations with behavioral and clinical measures. Most recently, data-driven machine-learning approaches to larger data sets have been able to classify visceral pain syndromes from healthy control subjects. Future studies need to identify the mechanisms underlying the altered brain signatures of chronic visceral pain and identify targets for therapeutic interventions.